2024
DOI: 10.1002/adma.202402012
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxide‐Derived Nanostructures: Scalable Synthesis, Characterization, Properties, and Potential Applications

Hussein O. Badr,
Michel W. Barsoum

Abstract: Metal oxide nanostructures have received an increasing attention owing to their unique chemical and physical properties along with their widespread applications in various fields. In this article, we provide an overview of our recent discovery – christened Hydroxides‐Derived Nanostructures, or HDNs – in which we react hydroxide aqueous solutions (mostly tetramethylammonium hydroxide, TMAH) at temperatures < 100 °C and under atmospheric pressure with various metal‐containing precursors to scalably prepare no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 142 publications
0
2
0
Order By: Relevance
“…The SEM micrograph shown in Figure A, clearly shows the 1D nature of our material. Based on these results, we conclude that our material is a 1DL titanate. , Figure B shows a high-resolution TEM image of our sample. The sample possesses a wire-like structure consistent with the SEM image, and black circle regions can be observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SEM micrograph shown in Figure A, clearly shows the 1D nature of our material. Based on these results, we conclude that our material is a 1DL titanate. , Figure B shows a high-resolution TEM image of our sample. The sample possesses a wire-like structure consistent with the SEM image, and black circle regions can be observed.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we discovered a simple, single pot, scalable method to make a truly one-dimensional, 1D, TiO 2 . Because the structure is that of lepidocrocite, we refer to this new form of TiO 2 as 1DL. Using a combination of X-ray diffraction, XRD, and high resolution transmission electron microscope (HRTEM) images, we concluded that the 1DL are nanofilaments (NF) 5 × 7 Å 2 in minimum cross-section and tens of nanometers in length. , Figure A shows a schematic of a single 1DL comprised of 2 × 2 edge shared TiO 6 octahedra.…”
Section: Introductionmentioning
confidence: 99%